2012
DOI: 10.1038/ajg.2012.53
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acupuncture Treatment on Cerebral Activity in Functional Dyspepsia Patients and Its Relationship With Efficacy

Abstract: Acupuncture and sham acupuncture have relatively different clinical efficacy and brain responses. Acupuncture treatment more significantly improves the symptoms and quality of life of FD patients. The more remarkable modulation on the homeostatic afferent network, including the insula, ACC, and hypothalamus, might be the specific mechanism of acupuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 36 publications
7
108
0
Order By: Relevance
“…In recent years, a considerable number of studies have been performed to establish the therapeutic roles of acupuncture in treating functional gastrointestinal diseases. [10][11][12] PC6 (Neiguan) and ST36 (Zusanli) are major acupuncture points for improving gastrointestinal motility disorders. 13 Electroacupuncture (EA) is a modified acupuncture technique in which small electric current is applied to the acupoints via the acupuncture needles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a considerable number of studies have been performed to establish the therapeutic roles of acupuncture in treating functional gastrointestinal diseases. [10][11][12] PC6 (Neiguan) and ST36 (Zusanli) are major acupuncture points for improving gastrointestinal motility disorders. 13 Electroacupuncture (EA) is a modified acupuncture technique in which small electric current is applied to the acupoints via the acupuncture needles.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have demonstrated the therapeutic effect of acupuncture in treating FD by a large-sample randomized trial, in which itopride and non-acupoint acupuncture were used as positive and negative controls [15.] Further, we explored the biological effects and cerebral glycometabolic responses elicited by acupuncture by using metabonomic and neuroimaging approaches [16,17.] However, retrospective analyses of the differences in treatment response between FD subgroups are still needed to identify the type and symptoms of FD that are more responsive to acupuncture treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Li/Zeng/Yang/Chen/Zhang/Sun/Qin/Yang/ Liang more, our previous PET-CT study demonstrated that acupuncture treatment could not only modulate the homeostatic afferent network, including the insula, ACC and hypothalamus, but it could also significantly improve the symptoms and quality of life of FD patients [15]. It is thus clear that the efficacy of acupuncture treatments for FD might result partly from modulating the functions of the homeostatic afferent processing network.…”
Section: Discussionmentioning
confidence: 99%